Uterine fibroids – what’s new? [version 1; referees: 3 approved] - Alistair R.W. Williams (F1000Research, 2017)
Uterine fibroids are the commonest benign tumours of women and affect all races with a cumulative lifetime risk of around 70%. Despite their high prevalence and the heavy economic burden of treatment, fibroids have received remarkably little attention compared to common female malignant tumours. This article reviews recent progress in understanding the biological nature of fibroids, their life cycle and their molecular genetic origins. Recent progress in surgical and interventional management is briefly reviewed, and medical management options, including treatment with selective progesterone receptor modulators, are also discussed.